Flux analysis of the Lactobacillus reuteri propanediol-utilization pathway for production of 3-hydroxypropionaldehyde, 3-hydroxypropionic acid and 1,3-propanediol from glycerol - Dishisha, Tarek (BioMed Central, 2014)
BACKGROUND: Lactobacillus reuteri converts glycerol to 3-hydroxypropionic acid (3HP) and 1,3-propanediol (1,3PDO) via 3-hydroxypropionaldehyde (3HPA) as an intermediate using enzymes encoded in its propanediol-utilization (pdu) operon. Since 3HP, 1,3PDO and 3HPA are important building blocks for the bio-based chemical industry, L. reuteri can be an attractive candidate for their production. However, little is known about the kinetics of glycerol utilization in the Pdu pathway in L. reuteri. In this study, the metabolic fluxes through the Pdu pathway were determined as a first step towards optimizing the production of 3HPA, and co-production of 3HP and 1,3PDO from glycerol. Resting cells of wild-type (DSM 20016) and recombinant (RPRB3007, with overexpressed pdu operon) strains were used as biocatalysts. RESULTS: The conversion rate of glycerol to 3HPA by the resting cells of L. reuteri was evaluated by in situ complexation of the aldehyde with carbohydrazide to avoid the aldehyde-mediated inactivation of glycerol dehydratase. Under operational conditions, the specific 3HPA production rate of the RPRB3007 strain was 1.9 times higher than that of the wild-type strain (1718.2 versus 889.0 mg/g(CDW).h, respectively). Flux analysis of glycerol conversion to 1,3PDO and 3HP in the cells using multi-step variable-volume fed-batch operation showed that the maximum specific production rates of 3HP and 1,3PDO were 110.8 and 93.7 mg/g(CDW).h, respectively, for the wild-type strain, and 179.2 and 151.4 mg/g(CDW).h, respectively, for the RPRB3007 strain. The cumulative molar yield of the two compounds was ~1 mol/mol glycerol and their molar ratio was ~1 mol(3HP)/mol(1,3PDO). A balance of redox equivalents between the glycerol oxidative and reductive pathway branches led to equimolar amounts of the two products. CONCLUSIONS: Metabolic flux analysis was a useful approach for finding conditions for maximal conversion of glycerol to 3HPA, 3HP and 1,3PDO. Improved specific production rates were obtained with resting cells of the engineered RPRB3007 strain, highlighting the potential of metabolic engineering to render an industrially sound strain. This is the first report on the production of 3HP and 1,3PDO as sole products using the wild-type or mutant L. reuteri strains, and has laid ground for further work on improving the productivity of the biotransformation process using resting cells.